2020
DOI: 10.1039/c9ra09126b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sludge electro-dewaterability during biological conditioning

Abstract: An effective deep dewatering process of coupling biological conditioning and electro-dewatering was proposed and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…By contrast, our previous study has confirmed that the catalytic activity of Pt@Cu bimetal nanocrystals with same metal molar ratios present evidently inferior catalytic activity to Pt@Cu(9%)/TiO 2 , [ 28 ] which should be undoubtedly attributed to the positive effect of the carrier TiO 2 –NTs. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, our previous study has confirmed that the catalytic activity of Pt@Cu bimetal nanocrystals with same metal molar ratios present evidently inferior catalytic activity to Pt@Cu(9%)/TiO 2 , [ 28 ] which should be undoubtedly attributed to the positive effect of the carrier TiO 2 –NTs. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, the noble metal components, especially their nanoagents, are prone to loss or agglomeration in the course of service, thus reducing their activity and working life. [ 14–16 ] Therefore, in recent years the studying focus in the related field has gradually shifted to noble/nonnoble metal supported catalysts, with the aim of realizing high dispersing and firm bonding for the active components on some suitable carriers, [ 17,18 ] reducing the cost of the catalyst, also improving the catalytic performance. Titanium dioxide (TiO 2 ), with abnormally high chemicophysical stability, satisfactory mechanical strength, and rich morphology, has been known as one kind of promising and competitive catalytic carrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation